Hepatoprotective And Antioxidant Activities Of The Edible Mushroom, (Agaricus Bisporus) On Carbon Tetrachloride-Induced Chronic Hepatitis In Rats (Journal of Pharmaceutical Negative Results, 2023)
In this study the hepatoprotective and antioxidant activities of the edible mushroom (white button mushroom, Agaricus bisporus), as a part of diet, were investigated in Wistar rats. Various biometric and biochemical parameters were examined. Chronic hepatitis model was induced by intraperitoneal (ip) administration of CCl4. Twenty-eight adult male albino rats were utilized in this experiment arranged randomly in four groups, seven rats each, as follows: The first main group (n= 7) rats were fed on basal diet and served as a negative control group. The second main group (n=21) rats were intraperitoneally injected by CCL4 dissolved in olive oil (in a dose of 0.5 mg/Kg) twice weekly for four weeks. These rats were distributed into three subgroups as follows: The first subgroup: fed on basal diet and served as a positive control group. The other subgroups fed on basal diet supplemented with 7.5% and 15% dried mushroom, respectively. At the end of the experimental period (6 weeks), rats were sacrificed and blood sampled were withdrawn then centrifuged to obtain then clear serum which used for biochemical analysis. Results indicated that diet supplementation with mushroom significantly (P<0.05) increased superoxide dismutase (SOD) enzyme and decreased malondialdehyde (MDA) levels. Diet supplementation with mushroom significantly (P<0.05) improved the activity of AST, ALT, ALP and total bilirubin and increased the concentrations of albumin and total protein, as well as improvement daily feed intake (FI), body weight gain percentage (BWG %) and feed efficiency ratio (FER). The obtained results from this study revealed that mushroom is a good antioxidant and hepatoprotective agent against carbon tetrachloride-induced chronic hepatitis in rats, which would be exploited as a potentially natural dietetic agent for hepatic protection, and it can be recommended for food and health applications aiming at reduction prospect oxidative stress.